CLASH—A Compliant Sensorized Hand for Handling Delicate Objects - Friedl, Werner; Roa, Máximo A. (Frontiers in Robotics and AI, 2020)
Automation of logistic tasks such as object picking and placing is one of the most active areas of research in robotics nowadays. Handle delicate objects such as fruits and vegetables, both in warehouses or in plantations, is a big challenge due to the delicacy and precision required for the task. This paper presents the CLASH hand, a Compliant Low Cost Antagonistic Servo Hand, whose kinematics was specifically designed for handling groceries. The main feature of the hand is the variable stiffness that allows it to withstand collisions with the environment, and also to adapt the passive stiffness to the object weight, while relying on a modular design using off-the-shelf low cost components. Due the implementation of differentially coupled flexors, the hand can be actuated like an underactuated hand, but also can be driven with different stiffness levels to planned grasp poses, i.e., it can serve for both model-based grasp planning or for underactuated or model-free grasping. The hand includes also self-checking and logging processes, which facilitates research and enables more robust performance during grasping actions. The paper presents key aspects of the hand design, examines the robustness of the hand in impact tests, and uses a standardized fruit benchmarking test to verify the behavior of the hand when different actuation and sensor failures occur and are compensated autonomously by the hand.